1996
DOI: 10.1128/mcb.16.10.5782
|View full text |Cite
|
Sign up to set email alerts
|

Direct Interaction between Protein Kinase Cθ (PKCθ) and 14-3-3τ in T Cells: 14-3-3 Overexpression Results in Inhibition of PKCθ Translocation and Function†

Abstract: Recent studies have documented direct interactions between 14-3-3 proteins and several oncogene and proto-oncogene products involved in signal transduction pathways. Studies on the effects of 14-3-3 proteins on protein kinase C (PKC) activity in vitro have reported conflicting results, and previous attempts to demonstrate a direct association between PKC and 14-3-3 were unsuccessful. Here, we examined potential physical and functional interactions between PKC theta, a Ca(2+)-independent PKC enzyme which is exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
123
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(130 citation statements)
references
References 62 publications
(109 reference statements)
6
123
1
Order By: Relevance
“…Transfection of Jurkat T-lymphoblastic Cells with pEF-PKC-His 6 and Purification on Ni 2ϩ Affinity Beads-Jurkat T ag cells are stably transfected with the SV40 large T antigen, which is used to promote expression of genes cloned in the pEF vector (16). pEF-PKC-contains the complete coding region of PKC-and an in-frame His 6 tag at the C terminus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transfection of Jurkat T-lymphoblastic Cells with pEF-PKC-His 6 and Purification on Ni 2ϩ Affinity Beads-Jurkat T ag cells are stably transfected with the SV40 large T antigen, which is used to promote expression of genes cloned in the pEF vector (16). pEF-PKC-contains the complete coding region of PKC-and an in-frame His 6 tag at the C terminus.…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant His 6 -PKC-Phosphorylates Moesin-To verify that PKC-phosphorylates moesin, we transfected eukaryotic cells with a plasmid bearing PKC-with a His 6 tag at its C terminus (16,29). Jurkat (T-lymphoblastic leukemia) cells were transfected with the His 6 -PKC-plasmid and with the neo vector alone.…”
Section: Fig 6 Partial Purification Of Pkc-from Aml Cellsmentioning
confidence: 99%
“…The 14-3-3 proteins have raised to a position of integrators of diverse signaling cues that impact cell fate and cancer development [31]. Through regulated interactions with crucial signaling mediators, such as PKC [32][33], MAPK [34][35][36], or AKT [37-39], 14-3-3 controls diverse cellular responses ranging from signal transduction, cell cycle, metabolism, and apoptosis [31]. Among seven 14-3-3 proteins, 14-3-3ζ, also termed as YWHAZ (tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein, zeta polypeptide), has been shown to play a central role regulating multiple pathways responsible for cancer initiation and progression [40].…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have reported that 14-3-3s act as potential regulators of PKC, which is controlled by the interactions between them [10][11][12][13]. However, the effects of 14-3-3 on PKC have been controversial, showing conflicting results of inhibition or activation [5,9,13], and the biological significance of this event remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this isotype is present in significant amounts in the retina, as well as in the brain, and is necessary for light adaptation processes or differentiation in photoreceptors [7,8]. It is well established that 14-3-3 proteins function as a protein kinase C (PKC) regulator [9][10][11][12][13]. In vitro, 14-3-3 ζ has been reported to be an endogenous PKC inhibitor [5,14], but the role of 14-3-3 ζ in the diabetic retina remains unclear.…”
Section: Introductionmentioning
confidence: 99%